In Italy compatibility between qualifying training objectives of degree courses in sport sciences and exercise and the kinesiologist profile - D'isanto, Tiziana; D'elia, Francesca; Altavilla, Gaetano; Aliberti, Sara; Esposito, Giovanni; Di Domenico, Felice; Raiola, Gaetano (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In Italy the 2021 sport reform established the new profession of kinesiologist, granted only to graduates of three-degree courses in sport sciences. The curricula of these degree courses, in addition to complying with training objectives to become a physical education (PE) teacher, must also be compatible with the profile of a kinesiologist. Aim of Study. The aims were two: 1) measuring the European credits transfer system (ECTS) of three training domains: sport and physical activity, biomedicine and psychopedagogy, to establish their consistency with kinesiology; 2) verifying the relationship between ECTS of the three training domains in all degree courses. Material and Methods. The sample was the whole population of degree courses in sport sciences in Italy. Central tendency and dispersion indices were estimated to analyze the ECTS score to achieve the first aim, while the Chi Square test was performed to achieve the second one. Results. The lower number of ECTS credits for sport and physical activity made the formation not congruent respecting the qualifying training objectives and the fluctuation of mean, median and mode values as well as standard deviation, made the formation even less compliant with respect to the three professional profiles of kinesiologist. Three significant relationships were identified among the ECTS of the three domains in two-degree courses, which therefore implied that they were probably part of the formation of the system. Conclusions. The study did not present limitations of sampling because the entire population was analyzed and the originality was high, because no similar study could be found in the literature.
Keywords: sports sciences; physical education; health; wellbeing; reform